2015
DOI: 10.1016/j.drugpo.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

High risk and little knowledge: Overdose experiences and knowledge among young adult nonmedical prescription opioid users

Abstract: Background Opioid-involved overdoses in the United States have dramatically increased in the last 15 years, largely due to a rise in prescription opioid (PO) use. Yet few studies have examined the overdose knowledge and experience of nonmedical PO users. Methods In depth, semi-structured, audio-recorded interviews were conducted with 46 New York City young adults (ages 18–32) who reported using POs nonmedically within the past 30 days. Verbatim interview transcripts were coded for key themes in an analytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 39 publications
3
91
0
Order By: Relevance
“…Research has found that young adults frequently use POs nonmedically with peers in social settings (e.g., at parties, while hanging out with friends) and young people report using POs to reduce anxiety, facilitate social interactions, enhance sexual experiences, and intensify the effects of other substances (Mateu-Gelabert, Guarino, Jessell, & Teper, 2015; McCabe, Cranford, Boyd, & Teter, 2007; Silva, Kecojevic, & Lankenau, 2013). When taken in large doses or in combination with other substances (e.g., benzodiazepines, alcohol), the effects of POs may lead to drowsiness, impaired judgment, incapacitation, loss of consciousness, and overdose (Frank etal., 2015; Jones, Mogali, & Comer, 2012; Lipman, 2010; Mateu-Gelabert et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Research has found that young adults frequently use POs nonmedically with peers in social settings (e.g., at parties, while hanging out with friends) and young people report using POs to reduce anxiety, facilitate social interactions, enhance sexual experiences, and intensify the effects of other substances (Mateu-Gelabert, Guarino, Jessell, & Teper, 2015; McCabe, Cranford, Boyd, & Teter, 2007; Silva, Kecojevic, & Lankenau, 2013). When taken in large doses or in combination with other substances (e.g., benzodiazepines, alcohol), the effects of POs may lead to drowsiness, impaired judgment, incapacitation, loss of consciousness, and overdose (Frank etal., 2015; Jones, Mogali, & Comer, 2012; Lipman, 2010; Mateu-Gelabert et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Among people who misuse substances, several studies have noted that individuals with multiple HIV transmission risk factors tended to perceive their personal risk of contracting HIV as low 1113 . A recent qualitative study found that people who misuse opioids other than heroin often perceive these opioids as being safe from the risk of overdose, even though most of the interviewees had experienced one or more overdoses in the past 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Given the recent increase in the number of Americans reporting nonmedical use of prescription opioids (SAMHSA, 2014a) – and emerging evidence that a growing proportion of nonmedical prescription opioid users are transitioning to heroin use (Frank, Mateu-Gelabert, Guarino, Bennett, Wendel, & Teper, 2014; Jones, 2013; Mars, Bourgois, Karandinos, Montero, & Ciccarone, 2013; Mateu-Gelabert, Guarino, Jessell, & Teper, A., 2014) – the demand for effective treatment for opioid use disorders is high and likely to intensify in the near future. Yet the vast majority of those who could benefit from treatment do not receive it.…”
mentioning
confidence: 99%